Implementasi Program Asuransi Usaha Tani Padi (AUTP) Dalam Meningkatkan Kesejahteraan Petani Di Kecamatan Ambalau Kabupaten Sintang - Segah, Antonius Tony; Yohanes, Yulius; Herlan, Herlan (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Writing a thesis in this study entitled: "Implementation of the Rice Farmers Insurance Program (AUTP) in Improving the Welfare of Farmers in Ambalau District, Sintang Regency". The aim of this research is To find out the implementation of the Rice Farmers Business Insurance Program (AUTP) in improving the welfare of farmers in Ambalau District, Sintang Regency. This is to determine the supporting and inhibiting factors for the Implementation of the Rice Farmers Business Insurance Program (AUTP) in improving the welfare of farmers in Ambalau District, Sintang Regency. The result of this research is the Organizing of the Farmers' Rice Business Insurance Program in Ambalau District, Sintang Regency. As a form of the government's support in protecting farmers from the risk of crop failure, the Ministry of Agriculture, starting in 2019, has implemented Rice Farming Insurance (AUTP). Rice farming insurance is expected to provide protection to farmers in the event of crop failure as a result of the risk of flooding, drought and pest attacks, transfer losses to other parties through insurance coverage, and be able to provide education to farmers in managing risks and a good farming system. One form of activity to ease farmers in paying premiums, in the early stages of expanding the AUTP trial, including providing premium assistance to farmers participating in AUTP. Interpretation of Organizing Farmers' Rice Business Insurance Program in Ambalau District Sintang Regency Location Criteria AUTP is implemented in irrigated rice fields (technical irrigation, semi-technical irrigation, rural / simple irrigation, and tidal / swampy swamps that already have a functioning water system) and rainfed lowland areas where water sources (surface water and groundwater) are available, prioritized in the area of ​​rice production centers, prioritized in the area where rice Upsus is administered and / or synergized with central government and regional government programs. The location is located in one stretch. Guaranteed Risk AUTP guarantees damage to the insured crops caused by flooding, drought, and pest attacks with the following limitations. Flooding is the inundation of agricultural land during a period of plant growth with a certain depth and period of time, thereby reducing crop production rates. Drought is the unfulfilled need for plant water during a period of plant growth which results in not optimal plant growth, thereby reducing the level of crop production. Plant Destruction Organisms (OPT) are organisms that can disturb and damage plant life or cause death in food plants, including inside: Plant pests: Stem borer, brown planthopper, stinker, rats, armyworms, and golden snails.